Penerapan Pembelajaran Kontekstual dengan Teknik Learning Community untuk Meningkatkan Minat dan Hasil Belajar Siswa Kelas V pada Pembelajaran PKn di SDN 3 Bumi Waras Semester 2 Tahun Pelajaran 2021/2022 - Azmawati, Azmawati (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2023)
This research is Classroom Action Research (PTK) with the application of contextual learning community learning techniques in Civics subjects. The formulation of the problem in this study is (1) Whether the application of contextual learning community learning techniques can increase student learning interest in learningCivics on Competency Standards (SK) respect the joint decision of grade V SD Negeri 3 Bumi Waras?; (2) Can the application of contextual learning community learning techniques improve student learning outcomes in Civics learning on Competency Standards (SK) respecting the joint decision of grade V SD Negeri 3 Bumi Waras? Based on the formulation of the problem above, the results showed that; (1) The application of contextual learning community learning techniques can increase students' interest in Civics learning on Competency Standards (SK) respecting the joint decision of grade V SD Negeri 3 Bumi Waras; (2) The application of contextual learning community learning techniques can improve student learning outcomes in Civics learning on Competency Standards (SK) respecting the joint decision of grade V SD Negeri 3 Bumi Waras.